1994
DOI: 10.1136/hrt.71.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Differences in autonomic nerve function in patients with silent and symptomatic myocardial ischaemia.

Abstract: Patients with silent ischaemia and pain pathways presumed to be intact have an enhanced peripheral vasodilator response, and if this applied to the coronary vasculature it could provide a mechanism for limiting ischaemia to below the pain threshold. Patients with pure silent ischaemia have evidence of sympathetic autonomic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 34 publications
0
16
0
1
Order By: Relevance
“…The mechanisms of painless myocardial ischemia are, however, complex and not fully understood. Altered pain thresholds, subthreshold ischemia not sufficient to induce pain, and dysfunction of the afferent cardiac autonomic nerve fibers have all been suggested as possible mechanisms (18). A recent investigation that used positron emission tomography to measure regional cerebral blood flow as an index of regional neuronal activation has shown that impaired afferent signaling resulting from autonomic dysfunction is associated with failed signal transmission from the thalamus to the frontal cortex (19).…”
Section: Painless Myocardial Ischemiamentioning
confidence: 98%
“…The mechanisms of painless myocardial ischemia are, however, complex and not fully understood. Altered pain thresholds, subthreshold ischemia not sufficient to induce pain, and dysfunction of the afferent cardiac autonomic nerve fibers have all been suggested as possible mechanisms (18). A recent investigation that used positron emission tomography to measure regional cerebral blood flow as an index of regional neuronal activation has shown that impaired afferent signaling resulting from autonomic dysfunction is associated with failed signal transmission from the thalamus to the frontal cortex (19).…”
Section: Painless Myocardial Ischemiamentioning
confidence: 98%
“…Altered pain thresholds, subthreshold ischemia not sufficient to induce pain, and dysfunction of the afferent cardiac autonomic nerve fibers have all been suggested as possible mechanisms. 32 Positron emission tomography to measure regional cerebral blood flow as an index of regional neuronal activation has shown that impaired afferent signaling resulting from autonomic dysfunction is associated with failed signal transmission from the thalamus to the frontal cortex. 33 In the Detection of Ischemia in Asymptomatic Diabetics (DIAD) study of 1123 patients with type 2 diabetes, cardiac autonomic dysfunction was a strong predictor of ischemia.…”
Section: Silent Myocardial Ischemia/cardiac Denervation Syndromementioning
confidence: 99%
“…Evidence of autonomic nerve dysfunction has also been described in non-diabetic patients with SI [27]. While peripheral neuropathy can explain some instances of SI, it should be noted that SI can also be observed in many non-diabetic persons who have no evidence of neuropathy.…”
Section: Pathogenesis and Pathophysiologymentioning
confidence: 94%